MODERN PEDAGOGICAL TECHNOLOGIES AND THE FORMATION OF COMPETENCE - Karimov Azizxon Azamjanovich (Modern World Education: New Age Problems – New solutions, 2026)
This study examines the role of modern pedagogical technologies in the formation of student competencies in contemporary education. It explores theoretical foundations, methodological approaches, and practical applications of various innovative educational strategies, including problem-based learning, project-based learning, blended learning, flipped classrooms, adaptive digital systems, and simulation-based instruction. The research highlights how these technologies foster cognitive, professional, digital, and socio-emotional competencies. The paper also discusses the challenges of implementation, such as digital inequality, teacher preparedness, and policy support. Empirical evidence and international educational frameworks confirm that competence-oriented education enhances critical thinking, problem-solving, creativity, collaboration, and lifelong learning skills.